The mechanism of ITGB4 in tumor migration and invasion - Huang, Guichen; Zhou, Minfeng; Lu, Damin; Li, Jinxiao; Tang, Qian; Xiong, Chutong; Liang, Fengxia; Chen, Rui (Frontiers in Oncology, 2024)
Integrin β4 (ITGB4) is a transmembrane protein that functions as a mechanosensor, mediating the bidirectional exchange of information between the intracellular and extracellular matrices. ITGB4 plays a critical role in cell adhesion, migration, and signaling. Numerous studies have implicated ITGB4 as a key facilitator of tumor migration and invasion. This review provides a foundational description of the mechanisms by which ITGB4 regulates tumor migration and invasion through pathways involving focal adhesion kinase (FAK), protein kinase B (AKT), and matrix metalloproteinases (MMPs). These mechanisms encompass epithelial-mesenchymal transition (EMT), phosphorylation, and methylation of associated molecules. Additionally, this review explores the role of ITGB4 in the migration and invasion of prevalent clinical tumors, including those of the digestive system, breast, and prostate.Cancer poses a significant social, public health, and economic burden. Data from the International Agency for Research on Cancer (IARC) indicate that roughly one in five individuals, both men and women, will develop cancer during their lifetime. Furthermore, approximately one in nine men and one in two women succumb to the disease(1). Metastasis, the spread of cancer cells from the primary tumor to distant organs, is the leading cause of death from cancer. Unlike primary tumors, metastasis represents a systemic disease affecting the entire body(2). Therefore, elucidating the mechanisms underlying tumor metastasis and identifying non-specific targets within the metastatic cascade are crucial for advancing cancer therapy.Integrins are heterodimeric transmembrane receptors composed of non-covalently associated α and β subunits. The human genome encodes 18 α and 8 β subunits, which